The Effect of Social Media Marketing and Electronic Word of Mouth on Purchase Decisions, with Brand Awareness as A Mediating Variable, at Mosa Coffee Garage - Damar Athala Raya; Vigory Gloriman Manalu (Cakrawala Repositori IMWI)
Competition among coffee shops in Bandung has become increasingly intense due to the rapid growth of coffee shop businesses and changing consumer behavior in digital environments. This study analyzed the effects of Social Media Marketing (SMM) and Electronic Word of Mouth (E-WOM) on Purchase Decisions, with Brand Awareness as a mediating variable at Mosa Coffee Garage. Using a quantitative associative approach with a survey method, an online questionnaire was distributed to 446 respondents who had previously purchased products at Mosa Coffee Garage. Data were analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS) through SmartPLS 4.0. The results showed that SMM (coefficient = 0.491; T-statistic = 17.815) and E-WOM (coefficient = 0.641; T-statistic = 24.222) had significant and positive effects on Brand Awareness. Brand Awareness demonstrated the strongest positive effect on Purchase Decisions (coefficient = 1.095; T-statistic = 29.755). Interestingly, SMM (-0.165) and E-WOM (-0.314) exhibited negative direct effects on Purchase Decisions; however, Brand Awareness successfully mediated these relationships through positive indirect effects (SMM?BA?PD = 0.537; E-WOM?BA?PD = 0.702). The R² values indicated that 68.9% of the variance in Brand Awareness and 67.9% of the variance in Purchase Decisions were explained by the proposed model. These findings confirm that digital marketing strategies are more effective in influencing purchase decisions when they first strengthen brand awareness rather than relying solely on direct promotional approaches that may generate consumer resistance.